Electronic voting systems for defending free will and resisting bribery and coercion based on ring anonymous signcryption scheme. (January 2017) - Hsiao, Tsung-Chih; Wu, Zhen-Yu; Liu, Chia-Hui; Chung, Yu-Fang
Vote by ballot is the feature in a democratic society and the process of decision-making, tending to achieve the philosophy of democratic politics by having the public who are eligible to vote for competent candidates or leaders. With the rapid development of technologies and network applications, electronization has been actively promoted globally during the social transformation period that the concept of electronic voting is further derived. The major advantages of electronic voting, comparing with traditional voting, lie in the mobility strength of electronic voting, reducing a large amount of election costs and enhancing the convenience for the public. Electronic voting allows voters completing voting on the Internet that not only are climate and location restrictions overcome, but the voter turnout is also increased and the voting time is reduced for the public. With the development in the past three decades, electronic voting presents outstanding performance theoretically and practically. Nevertheless, it is regrettable that electronic voting schemes still cannot be completely open because of lures by money and threats. People to lure by money and threats would confirm the voters following their instructions through various methods that more factors would appear on election results, affecting the quality and fairness of the election. In this study, this project aims to design an electronic voting scheme which could actually defend voters' free will so that lure of money and threats would fail. Furthermore, an electronic voting system based on Elliptic Curve Cryptography is proposed to ensure the efficiency and security, and Ring Signature and Signcryption are applied to reducing the computing costs. Moreover, this project also focuses on applying voting system to mobile devices. As the system efficiency and security are emphasized, voters do not need to participate in the election, but simply complete voting with smart phones, iPads, and computers. The votes would be automatically calculated and verified the results that the ballots are not necessarily printed, the printing of election mails is reduced, and manual handling is canceled. Such a method would effectively reduce voting costs and enhance the economic efficiency.